(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Immumomodulatory actions of natural ingredients have been recognized from the time of early civilization. Though herbal medicines are equally used to treat deadly diseases, but till date there are lacks of evidences. In the present work, an herbal preparation IMT-03 was used to find out its immunostimulatory efficacy against chemotherapeutics. Although, most of the individual ingredients present in IMT-03 have been reported for their protective roles against chemotherapeutics, but there is no report in combination. Cyclophosphamide (300 mg/kg, intraperitoneally) induces immunosuppression through myelosuppression. Pretreatment with of IMT-03 at dose of 100 mg/kg and 200 mg/kg in Cyclophosphamide induced immunosuppressive mice showed dose dependently and significantly (p<0.001) improvement in total WBC and absolute neutrophil counts. It also protects the general health of animals from chemotherapeutic induced serious adverse events like signs of sickness, lethargy, immobility, reducing food habit, infections in nostrils and pinna etc. Moreover, IMT-03 has the abilities to counter the macrophages surge during the LPS challenge. The test drug also showed safe up to the oral dose of 2 g/kg. In vitro studies revealed IMT-03 has polyphenols and also radical scavenging actions. There are several evidences that polyphenols can able to modulate cytokines and chemokines signaling pathways in immune cells. Therefore, it is assumed that polyphenols present in IMT-03 either modulate the inflammatory signaling pathways or protect from oxidative stress related DNA damage in myeloid tissues.